The metaphor as a methodological alternative to investigate and reflect on the pedagogical practice in the teaching of reading and writing - Valenciano-Canet, Grettel (2019)
This article synthesizes the results of a qualitative study, whose objective was to analyze the strategies that a first-grade teacher uses to promote the process of motivation of girls and boys in their class, towards learning to read and write. The metaphor technique is used as a methodological alternative in order to reflect on the pedagogical practice, also integrating the techniques of participant observation, interview and the theoretical foundations. A qualitative design was used, which was adapted to the object of study during the process. The article summarizes the analysis and discussion of the results, with the organization of the information, which is oriented to the elaboration of categories that give unity to the data collected during the research process, evidencing that the findings are conducive to the achievement of the objective presented. In conclusion, it is shown that the pedagogical practice of the teacher participating in this study is located in the positivist paradigm and the behavioral approach to learning. This view is contrary to the integral language proposal. It is considered important to carry out transformations in the Costa Rican formal education system. For this, it is necessary to reflect on pedagogical practices, which involve the belief systems, worldviews, and theoretical conceptions of teachers. Finally, it is worth mentioning that the author of the article is the researcher.